Power Factor Correction Using Single Stage Discontinuous Conduction Mode Booster Rectifier - Athab, Hussain Sabri (2003)
A single stage three-phase power factor correction circuit using a boost input current shaper has been described in both simulation and experimental work. To reduce the cost and avoid complexity the boost dc-to-dc converter is operated in discontinuous conduction mode using only one active switch. A low cost harmonic injection method for single switch three-phase DCM boost rectifiers has been simulated and tested. In this method, a periodic voltage which is proportional to the inverted ac component of the rectified three-phase line-to-line input voltage is injected in the control circuit to vary the duty cycle of the rectifier switch within a line cycle, so that the fifth-order harmonics of the input current is reduced to meet THD<10% requirement.The analysis of the injected signal and modified harmonic currents of the rectifier has been presented and verified on a laboratory prototype. Based on the equivalent multimodel an average small signal model of the boost power stage is developed and verified by simulation. The variations of the small signal model against load are demonstrated, and the compensator designed for constant switching frequency PWM is discussed. The simulated results show that at light load, the dominant pole of the control-to-output transfer function approaches the origin and causes more phase delay, complicating the control design circuit. To avoid the no load case and simplify the control design, a dummy is added. The single stage three-phase boost power factor correction with improved input current distortion has been simulated using OrCad release 9.1 software. The results show there is an agreement between the simulation and experimental work.